46.2: A Novel Laminated Organic Light‐Emitting Diodes with a Multi‐Layered Graphene Top Anode. Issue 1 (June 2015) - Lee, Hyunkoo; Lim, Jong Tae; Cho, Nam Sung; Lim, Seong Chu; Kwon, Byoung‐Hwa; Cho, Hyunsu; Han, Jun‐Han; Yu, Byoung‐Gon; Lee, Jeong‐Ik
Abstract : We report on a novel fabrication method for organic lightemitting diodes (OLEDs) by using a multilayered graphene (MLG) film and a lamination technique. The OLED structure with the MLG top electrode has higher transmittance and lower reflectance than the OLED structure with the conventional thin metal electrode. Moreover, higher luminous current efficiency of the device with the MLG top electrode has been achieved compared with that of the conventional bottom‐emission OLEDs with aluminum metal electrode.